Regulasi Emosi Guru dan Menjadi Pendidik yang Profesional - Rozi Sastra Purna; Dwi Puspasari (Warta Pengabdian Andalas, 2022)
A teacher is a person who imparts knowledge to students. Teachers are subjects that play an essential role in the continuity of education. Teachers will be able to educate and teach if they have emotional stability and have a great sense of responsibility to advance their students. Teachers in schools must be able to deal with the emotional demands of the surrounding environment on an ongoing basis. Thus, the teacher's knowledge and skills are needed to manage the emotion they experience while carrying out their roles as educators. This community service activity was conducted at the Insan Karima Cendekia Foundation in Bukittinggi, West Sumatra. This location was chosen because it considered the problems faced by teachers, especially in managing emotions. The foundation also conveyed the obstacles and needs related to psychoeducation for teachers. The activities were packaged in the form of providing psychoeducation and direct practice related to emotional regulation and becoming professional educators. Through the activities carried out, it was hoped that it could be a means to help teachers recognize emotion and understand how to regulate their emotions and help teachers gain knowledge related to being a professional educator.